2014
DOI: 10.1155/2014/250540
|View full text |Cite
|
Sign up to set email alerts
|

Rollover Car Crashes with Ejection: A Deadly Combination—An Analysis of 719 Patients

Abstract: Rollover car crashes (ROCs) are serious public safety concerns worldwide. Objective. To determine the incidence and outcomes of ROCs with or without ejection of occupants in the State of Qatar. Methods. A retrospective study of all patients involved in ROCs admitted to Level I trauma center in Qatar (2011-2012). Patients were divided into Group I (ROC with ejection) and Group II (ROC without ejection). Results. A total of 719 patients were evaluated (237 in Group I and 482 in Group II). The mean age in Group I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Our data showed that a significantly higher percentage of ejection victims required cranial or spinal procedures, which coincides with previous studies identifying increased head and neck injuries in ejected victims [ 27 , 28 ]. Therefore, a high index of suspicion should be maintained when evaluating ejected patients in the acute setting, and liberal imaging for early identification of these injuries is warranted.…”
Section: Discussionsupporting
confidence: 92%
“…Our data showed that a significantly higher percentage of ejection victims required cranial or spinal procedures, which coincides with previous studies identifying increased head and neck injuries in ejected victims [ 27 , 28 ]. Therefore, a high index of suspicion should be maintained when evaluating ejected patients in the acute setting, and liberal imaging for early identification of these injuries is warranted.…”
Section: Discussionsupporting
confidence: 92%
“…The identification of Pillar 3, safer vehicles, as a gap in the implementation of the DoARS Action Plan in Qatar has important local implications. In Qatar, more than 40% of RTIs occur in the context of rollover crashes with 33% of these being ejected from the vehicle 46. Many of these rollover crashes and more of the attendant injuries could be prevented through the universal deployment of improved vehicle safety technologies, that is, Electronic Stability Control (ESC), for both passive and active safety through a combination of harmonization of relevant global standards, consumer information schemes and incentives to accelerate the uptake of new technologies 47.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that being in a vehicle rollover did not significantly increase the odds of being classified as a high acuity patient (OR=1.04; 95% CI, 0.75-1.43), while others have found that vehicle rollover is a criterion with suitable predictive ability (for trauma team activation) (30). Previous studies have suggested that using rollovers as a dispatch criterion to identify the acuity of patients could be improved when combined with other crash characteristics (31) such as whether the patient remained in the vehicle or was ejected (32). The crash characteristics identified in this study need to be further explored regarding their suitability to be used to determine ambulance dispatch priority.…”
Section: Discussionmentioning
confidence: 99%